THE INFLUENCE OF WORK ENVIRONMENT AND MOTIVATION ON EMPLOYEE PERFORMANCE IN WOOD FACTORY - Teddy Andrianto; Joshua Pandapotan Siringoringo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This research was conducted to analyze the influence of the environment and motivation on employee performance. The sample used was saturated sampling with 50 respondents. The results of this study indicate that the work environment and motivation have a significant effect on the performance of the Timber Mill with work motivation as the dominant variable. This research uses a quantitative approach and this research data is obtained through a questionnaire.